2005
DOI: 10.1097/00000542-200501000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Surgical Regional Anesthesia in the Ambulatory Setting: An Analysis of 9,038 Blocks

Abstract: The present investigation shows that obesity is associated with higher block failure and complication rates in surgical regional anesthesia in the ambulatory setting. Nonetheless, the rate of successful blocks and overall satisfaction remained high in patients with increased BMI. Therefore, overweight and obese patients should not be excluded from regional anesthesia procedures in the ambulatory setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(78 citation statements)
references
References 17 publications
2
67
1
8
Order By: Relevance
“…Above observations can be beneficial for anaesthesiologist providing regional anaesthesia for operations where short motor block is essential for early evaluation of surgical effect of tendons repair. Our finding is similar to Nielsen et al [34], who attempted to assess the impact of body mass index on 6,920 patient outcomes (block efficacy, rate of acute complications, postoperative pain at rest and with movement, postoperative nausea and vomiting, rate of unscheduled hospital admissions, and overall patient satisfaction) after ambulatory regional anaesthesia. Their study revealed that obesity was not associated with higher rate of postoperative pain at rest when compared with patients with a normal body mass index receiving different regional blocks performed with different ultrasound-guided techniques.…”
Section: Motor Block Terminationsupporting
confidence: 88%
“…Above observations can be beneficial for anaesthesiologist providing regional anaesthesia for operations where short motor block is essential for early evaluation of surgical effect of tendons repair. Our finding is similar to Nielsen et al [34], who attempted to assess the impact of body mass index on 6,920 patient outcomes (block efficacy, rate of acute complications, postoperative pain at rest and with movement, postoperative nausea and vomiting, rate of unscheduled hospital admissions, and overall patient satisfaction) after ambulatory regional anaesthesia. Their study revealed that obesity was not associated with higher rate of postoperative pain at rest when compared with patients with a normal body mass index receiving different regional blocks performed with different ultrasound-guided techniques.…”
Section: Motor Block Terminationsupporting
confidence: 88%
“…The accuracy of identifying a lumbar interspace using palpation is impaired by obesity but not by patient position [33]. In a large series of regional blocks performed at one ambulatory surgery center, patients with the highest BMI had significantly increased block failure rates compared to those with normal BMIs [32]. In anticipating the technical difficulty of performing a neuraxial block, correct identification of landmarks and detection of anatomical deformities were more significant predictors than body habitus, although there may be an association between BMI and quality of landmarks [34].…”
Section: Anatomymentioning
confidence: 99%
“…Multiple factors, from identification of anatomical landmarks to availability of appropriate equipment, can make these procedures technically difficult. In spite of these challenges, the incidence of procedure-related complications in obese patients is actually quite low, and obesity itself should never be a contraindication to regional anesthesia for appropriate cases [32]. Surface ultrasound can assist the clinician when performing neuraxial and peripheral nerve blocks.…”
Section: Challengesmentioning
confidence: 99%
“…So wurden 9038 Regionalanästhesien (periphere Blöcke der oberen und unteren Extremitäten, paravertebrale Blöcke, Spinal-und Epiduralanästhesien, lumbaler Plexusblock, Blockade des N. ischiadicus) bei 6920 Patienten ausgewertet (BMI <25 kg/m 2 bei 34,8%; BMI 25-29 kg/m 2 bei 34,0%; BMI ≥30 kg/m 2 bei 31,3%; [15] OR 1,9;[27]). Aufgrund dieses erhöhten Risikos für respiratorische Ereignisse im Rahmen der Allgemeinanästhesie ist auch bei Kindern die Durchführung eines Regionalanästhe-sieverfahrens eine im Einzelfall sinnvolle Alternative, wie von Legrand u. Tobias [11] in einer Fallserie über Narkosen bei adipösen Kindern (n=4, Prader-Willi-Syndrom), dargestellt wurde.…”
Section: Regionalanästhesieunclassified